iScan Campus: Revolutionizing Lab Asset Management Using RFID Technology - Adil Mohd Hafiz; Nora Syafira Abd Gani; Nur Syasya Fatimah Othman; Soosay Nathan, Shelena; Suwimol Jungjit (Multidisciplinary Applied Research and Innovation, 2025)
One of the rapidly developing trends in the modern world is the Internet of Things (IoT) – the concepts that define the use of physical objects for communication according to their function and context in the commercial, healthcare, transport, and home environments. Challenges arising from manual inventory management are well felt in learning institutions, especially where there is a lot of equipment in use each time such as computer laboratory. These challenges are mitigated in this project by suggesting an iScan Campus RFID-based inventory management system that rest established accuracy, efficiency and accountability in the inventorying management section. The system is installed with RFID tags and readers; thus, it provides efficient time-based tracking and management of equipment, thereby reducing equipment loss and optimizing the use of resources. The research employs the Agile software development approach that makes the development of the system flexible and able to accommodate changes in the requirements. The study therefore strongly supports the possibility of radio frequency identification technology as an effective tool of automated system of inventories, hence more deployment in similar events.